KETERSEDIAAN SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SMA NEGERI KABUPATEN SUMENEP - WIJAYA, FARIS (Jurnal Pendidikan Olahraga dan Kesehatan, 2017)
Abstrak Physical education, sports, and health are parts of the whole education system in physical activities. The implementation of developing physical education, sports, and health it’s a crucial thing to increase teaching and learning process to make it more effective and efficient. The availability of facilities and infrastructure are the main aspects to accelerating physical education, sports, and health learning process. This research were done to know the condition of the availability of facilities and infrastructure learning in Sumenep State Senior High School using instrument Pangkalan Data Pendidikan Jasmani Olahraga Indonesia (PDPJOI). PDPJOI instrument have 4 aspect, that aspects is : 1. Availability of facilities and infrastructure 2. Availability of  executive staff. 3. The result of 1 year past work. 4. The achievment of 1 year past. This Research only focus on scoring the availability of facilities and infrastructure in Sumenep State Senior High School. The recapitulation result of data of the availability of  sport facilities and infrastructure in Sumenep State Senior High School on average obtain score 115 which categorized as “C” (Cukup). Key word: The Availability of facilities and infrastructure for physical health education in Sumenep State Senior High School. Abstract Physical education, sports, and health are parts of the whole education system in physical activities. The implementation of developing physical education, sports, and health it’s a crucial thing to increase teaching and learning process to make it more effective and efficient. The availability of facilities and infrastructure are the main aspects to accelerating physical education, sports, and health learning process. This research were done to know the condition of the availability of facilities and infrastructure learning in Sumenep State Senior High School using instrument Pangkalan Data Pendidikan Jasmani Olahraga Indonesia (PDPJOI). PDPJOI instrument have 4 aspect, that aspects is : 1. Availability of facilities and infrastructure 2. Availability of  executive staff. 3. The result of 1 year past work. 4. The achievment of 1 year past. This Research only focus on scoring the availability of facilities and infrastructure in Sumenep State Senior High School. The recapitulation result of data of the availability of  sport facilities and infrastructure in Sumenep State Senior High School on average obtain score 115 which categorized as “C” (Cukup). Key word: The Availability of facilities and infrastructure for physical health education in Sumenep State Senior High School.